Analisis Keuntungan Pedagang Sayur Keliling Di Kelurahan Lawangirung Kecamatan Wenang Kota Manado - Pangkey, Ebenhaezer; Sondakh , Mex Frans; Tambas, Jane Sullida (AGRI-SOSIOEKONOMI, 2024)
The purpose of this study was to determine how much profit mobile vegetable traders in Lawangirung Village, Wenang Subdistrict, Manado City in a week. The research was conducted from July to August 2023. This research took place in Lawangirung Village, Wenang Subdistrict, Manado City. The data used in this study, namely primary data obtained using interview techniques in the form of questions provided directly to mobile vegetable traders, and secondary data in the form of data collected from the internet such as data from the Central Statistics Agency, scientific journals, theses, and books. Sampling in this study was selected accidentally (accidental sampling) to 4 samples of itinerant vegetable traders in Lawangirung Village, Wenang Subdistrict, Manado City. The data obtained in this study were analyzed using descriptive analysis and presented in tabular form. Meanwhile, to determine the profit of itinerant vegetable traders who sell their merchandise, profit analysis is used. The results showed that the average profit of itinerant vegetable traders who traded in Lawangirung Village, Wenang Subdistrict, Manado City in a week was IDR862,704.